The impact of structural adjustment programmes upon the political economy of Zambia: a critical analysis - Makan, Amita (Rhodes University, Faculty of Humanities, Department of Political Studies, 1994)
This study begins with a statistical survey setting out the parameters of Zambia's socio-economic decline in the 1980s. In order to unravel the complex reasons for the crisis, the study develops and employs an historical structural framework which emphasises the interconnectedness of historical, political, economic and social processes . Thereafter, an explanation of Zambia's political and economic development is presented as a background for understanding how and why the IMF came to play an increasingly decisive role in the management of the economic crisis in the 1980s. It is argued that patron-client politics in conjunction with a 'coincidence of interests' between local elite and international capital, entrenched the distorted mono-export dependent economy which, in turn, accelerated the economic decline and debt crisis of the 1980s. After presenting an overview of the Fund's philosophy and objectives, close attention is paid to the impact of SAPs on Zambia, especially in terms of how such policies as subsidy withdrawal, de-regulation and devaluation affected the economy, debt-reduction, health and education. While there is no incontrovertible evidence that adjustment policies caused the crisis, they have been largely ineffective in reversing Zambia's economic decline. In fact, due to the IMF's ahistorical and apolitical approach, any gains have been ephemeral and, in many instances, served to exacerbate the suffering of the population. Finally, Zambia's political structures have proved unable and unwilling to implement IMF reforms consistently and this underlies the central point that SAPs, as a strategy, cannot ensure long-term sustainable development.
Keywords: Structural adjustment (Economic policy) -- Zambia; Zambia -- Economic conditions -- 1964-; Zambia -- Politics and government -- 1964-1991; Zambia -- Economic conditions